Membangun Karakter Anak: Integrasi Budaya Lokal dan Nilai Pancasila di PAUD Ramah Anak - Arkam, Rohmad; Suprapto; Moh. Zainul Arifin (Institut Agama Islam Negeri Madura, 2024)
This research aims to determine strategies for developing the profile of Pancasila students through local culture to create child-friendly schools. The method used in this research is descriptive qualitative using data analysis techniques, data reduction, data display and conclusion drawing. Planning for a learning project to strengthen student profiles at TK Muslimat NU 089 goes through the stages; 1) teacher discussion, 2) taking project themes, 3) taking project learning paths, 4) making project teaching modules, 5) implementing project activities, 6) procuring infrastructure. Implementation of project activities at Muslimat NU 089 Kindergarten using three stages, namely; initial stage, development stage, conclusion stage and follow-up stage. Meanwhile, the evaluation learning project for strengthening the profile of Pancasila students at TK Muslimat NU 089 uses three stages, namely; 1) class assessment using a portfolio to analyze the dimensions of the Pancasila student profile that emerged during project learning, 2) carrying out a work title to showcase students' products, and 3) teacher reflection to analyze supporting and inhibiting factors for project activities.